Dinamika Kebijakan Pendidikan di Indonesia: Sebuah Analisis Administratif - Jackson Yumame; Loso Judijanto; Sufia Widi Kasetyaningsih (CV. ADIBA AISHA AMIRA, 2024)
The dynamics of Education Policy in Indonesia are experiencing changes and challenges in Indonesia. The study in this research uses the literature method. The results showed that; first, Consistent Policy Change: Education policy in Indonesia has gone through various phases of change in response to social, economic and political developments. These policies include increasing access to education, equalising quality and integrating technology in the teaching and learning process. Secondly, the education gap: Despite efforts to equalise access to education, this study found that there are still significant gaps between urban and rural areas and between different socio-economic groups. These gaps result in disparities in the quality of education received by students. Thirdly, resource management: One of the major challenges identified is the limitations in resource management, both human and financial. The lack of qualified teaching staff and adequate education infrastructure are major obstacles to effective education policy implementation. Fourth, Policy Implementation: The study found that although education policies are formulated comprehensively, their implementation is often inconsistent due to a lack of coordination between levels of government and weak supervision. This results in policies that are good on paper not always producing the expected results in the field.